The Effectiveness of Explanatory Videos on LMS in Enhancing EFL Students’ Comprehension: A Student-Centered Perspective - Adani Nur Sabrina (International Journal Multidisciplinary Science, 2025)
The integration of technology in education has led to the adoption of blended learning approaches, combining on-site and online modes. Among these, asynchronous learning offers more flexibility but limits student-teacher interaction. To address this gap, the researcher explores whether explanatory videos can effectively replace the lecturer’s presence in enhancing student comprehension. This study aims to evaluate the effectiveness of explanatory videos in improving student understanding, assess students' perceptions of video usage in the Learning Management System (LMS), and gather alternative methods to support learning beyond videos and presentations. Using a descriptive qualitative approach, the research presents data through visual charts and discussions. Data were collected via a questionnaire filled out by students. The findings indicate that while not all students watched the provided video, the majority believe that explanatory videos serve as valuable supplementary resources in the LMS, offering on-demand access for further clarification. This study contributes to the field of digital learning by offering insights into how explanatory videos can enhance student comprehension and by providing practical recommendations for improving digital learning environments.